Primary Distrust: Political Distrust and Support for the Insurgent Candidacies of Donald Trump and Bernie Sanders in the 2016 Primary. Issue 2 (4th April 2018) - Dyck, Joshua J.; Pearson-Merkowitz, Shanna; Coates, Michael
ABSTRACT: Donald Trump dominated the 2016 Republican primary despite the fact that he was not, in any meaningful sense, a Republican. Bernie Sanders came just shy of winning the Democratic nomination despite the fact that he switched his party affiliation from Independent to Democrat only three months before the election. Why did two candidates with no formal ties to the political parties fare so well? One possibility is that primary voters are more ideologically extreme and that ideology drives support for these candidates. However, another possibility is that concerns about government process drives support for insurgent candidates. We test the proposition that distrust was the primary motivator of primary voting for these two insurgent candidates using two datasets: a poll of New Hampshire voters fielded a week before their primary and a national poll taken in June 2016. Results confirm the hypothesis that distrust drove intraparty vote choice in the 2016 presidential primaries.